The Influence Of Gen Z’s Interest In Adventure As A Sustainable Tourism - Lubis, Muhammad Rizki; Rambe, Bunga Marisa; Fahrezi, M. Panji; Putri, Risyah Andira; Samosir, Rustina Evangelista; Dermawan, Anasya Mutiara (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2025)
Generation Z is an influential in the tourism industry. Nowadays, their behavior can influence travel preference and perceptions in supporting sustainable tourism development. This generation is also considered a more environmentally conscious generation, so environmental conservation efforts and the implementation of sustainable tourism practices in a destination can increase positive perceptions of the destination. In addition, in the future they will actively participate as tourism stakeholders, by taking into account the factors that will influence and take appropriate measures, it can strengthen its attractiveness Asia cultural tourism destination and take strategic steps for increased sustainable tourism development efforts. For this reason, this study seeks to reveal the factors that influence Generation Z's interest in efforts to increase sustainable tourism at the Pelaruga tourist attraction. The researchers employed qualitative research based on an ethnographic approach. The data collection methods employed observation and in-depth interviews. 2 interview sources, 6 interviewers, and 25 subjects were used to collect the questionnaire. Respondents were selected using purposive sampling, which involves selecting subjects based on characteristics that meet the stated objectives. The results of this study found that Pelaruga tourist attraction has provided a pleasant experience for tourists and has the potential to be developed Asia tourist attraction with the application of the principles of sustainable tourism principles. As well as contributing to supporting economic improvement for local communities. However, environmental preservation strategies are still need to be developed and planning needs to be done to collaborate with the government and local tourism organizations.